Crocodylian Distribution and Habitat Use in Western Sarawak - Pine, Anthony K.; Das, Indraneil (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Research was conducted within four river systems in western Sarawak, to identify and relate subaquatic habitat types to the distribution and abundance of two crocodylian species, Crocodylus porosus and Tomistoma schlegelii. Through the use of side-scan sonar, this study was able to peer into some of these turbid and mysterious riverways, providing some of the first glimpses into what exactly is beneath the waterline. This study utilised eyeshine surveys, captures and sonar mapping to acquire data necessary to fulfill its research objectives. The results include outputs for density and distribution patterns for crocodiles in targeted rivers of western Sarawak, comprehensive sonar mosaics detailing river profiles and GIS habitat maps useful for categorizing and quantifying subaquatic habitat types in Sarawak. This research sets the foundation for long-term research and monitoring effort for the crocodylians in Sarawak.